The single-cell immune landscape of HIV-associated aggressive B-cell lymphoma - Xiaomei Zhang; Zailin Yang; Xiaoqing Xie; Jun Li; Qing Xiao; Guofa Xu; Ben Ma; Xudong Xie; Yi Liu; Liuyue Zhai; Yifeng Tang; Huihui Fu; et al. (Journal of the National Cancer Center)
Background: Human immunodeficiency virus (HIV)-associated lymphomas (HAL), mainly aggressive B-cell lymphomas, pose a significant challenge in cancer research due to their multifaceted pathogenesis and aggressive clinical course. Despite the clinical importance, the genomic and immune characteristics of these lymphomas remain poorly elucidated. Methods: We employed single-cell RNA sequencing (scRNA-seq) on lymph node samples from aggressive B-cell lymphomas, mainly including 6 cases of diffuse large B-cell lymphoma (DLBCL) and 5 cases of Burkitt lymphoma (BL) from people living with HIV (PLWH), along with 3 DLBCL cases from individuals without HIV for comparison. Results: Malignant B cells in HAL consistently exhibited high proliferative and oxidative phosphorylation (OXPHOS)-type metabolic signatures. Moreover, these cells demonstrated loss expression of major histocompatibility complex class I (MHC-I), strategically reducing tumor immunogenicity. HAL harbors special populations of naive and atypical memory B cells that exhibited high metabolic and immune-activated transcriptional profiles. Additionally, HAL exhibited senescence-like dysfunction in T cells, characterized by the reductions in regulatory activity of Treg and cytotoxic activity of CD8+ T cells, as well as decreases expression of IL7R genes and increases expression of FOS and FOSB genes. Our immunofluorescence results showed that the cytotoxic CD8+ T cells in HAL may have a dysfunction of lytic granule polarization. Furthermore, macrophages from HAL exhibited stronger immunosuppressive transcriptional characteristics, and a robust immunosuppressive SPP1-CD44 interaction was predicted between C1QA+ macrophages and T cells. Conclusions: Our findings clearly indicate that HAL differs significantly from non-HAL, ranging from malignant B cells to the immune microenvironment. This study provides a comprehensive single-cell atlas of HIV-associated aggressive B-cell lymphomas, offering new insights into aggressiveness and immune evasion observed in HAL.